Chest wall dose assessment in stereotactic ablative radiotherapy delivered with volumetric modulated arc therapy for peripheral lung tumors. (2016) - Chi, Alexander; Wen, Sijin; Monga, Manish; Almubarak, Mohammed; Tse, William; Remick, Scot C.; Nguyen, Nam P.
Abstract: Background: No consensus on how to best predict for chest wall injury following SABR exists. We report our experience in chest wall dose assessment when treating peri-pleural lung lesions with stereotactic ablative radiotherapy (SABR) delivered with volumetric modulated arc therapy (VMAT). Methods: 40 patients with peri-pleural peripheral lung tumors underwent SABR between July, 2012 and February, 2015. Chest wall toxicity, dose distribution, and the influence of chest wall delineation method were investigated. Results: After a median follow up of 16 months, no rib fracture or skin toxicity was observed. 4 patients (10%) reported persistent chest wall pain (grade 1–2). High dose rate's association with chest wall pain trended toward statistical significance ( p =0.06). PTV exclusion and reducing chest wall expansion to 1 cm led to significant dose reduction in the chest wall dose volume parameters ( p <0.05). Only three local failures were observed among 44 lesions treated. Conclusions: The risk of chest wall pain following SABR delivered with VMAT is low. High dose rate, which is 1400 MU/min with flattening filter free (FFF) beams vs. 500–600 MU/min with non-flattening filter free (non-FFF) beams, may contribute to it. Chest wall dose volume parameters may vary with PTV exclusion; while chest wall expansion of 1 cm may fail to account for some high dose regions in the chest wall.